2008
DOI: 10.1126/science.1163174
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Switch of Syntaxin-1 Controls Synaptic Vesicle Fusion

Abstract: During synaptic vesicle fusion, the SNARE-protein syntaxin-1 exhibits two conformations that both bind to Munc18-1: a ‘closed’ conformation outside the SNARE-complex, and an ‘open’ conformation in the SNARE-complex. Whereas SNARE-complexes containing ‘open’ syntaxin-1 and Munc18-1 are essential for exocytosis, the significance of ‘closed’ syntaxin-1 is unknown. Here, we generated knockin/knockout mice that expressed only ‘open’ syntaxin-1B. Syntaxin-1BOpen mice were viable, but succumbed to generalized seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
345
6
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 262 publications
(392 citation statements)
references
References 22 publications
35
345
6
6
Order By: Relevance
“…S6), thereby limiting the number of v-vesicles available for docking. Recently, it was suggested that synaptobrevin-2 is not required for the initial docking of synaptic vesicles to the plasma membrane in vivo (46,47). Our results show that large α-Syn oligomers specifically inhibit SNARE complex formation between synaptobrevin-2 and t-SNAREs after initial docking by other synaptic factors, such as synaptotagmin-1, in the neuron.…”
Section: Discussionsupporting
confidence: 56%
“…S6), thereby limiting the number of v-vesicles available for docking. Recently, it was suggested that synaptobrevin-2 is not required for the initial docking of synaptic vesicles to the plasma membrane in vivo (46,47). Our results show that large α-Syn oligomers specifically inhibit SNARE complex formation between synaptobrevin-2 and t-SNAREs after initial docking by other synaptic factors, such as synaptotagmin-1, in the neuron.…”
Section: Discussionsupporting
confidence: 56%
“…Besides participating in SNARE complexes, syntaxin (Synt) is also involved in docking of granules. Synt1A knockout mice have a reduced number of docked granules (14), a fact that is in line with studies in chromaffin cells (31) and with the findings that interaction between Munc18-1, granuphilin and Syntaxin-1 is involved in docking of granules in insulin-secreting cells (32,33), and that the Munc18 -1-Syntaxin-1 complex is crucial for docking of granules in chromaffin cells (34)(35)(36).…”
supporting
confidence: 73%
“…Membrane proteins extracted from the LDCV-enriched fractions, which were confirmed by electron microscopy (Supplementary information, Figure S1B), were processed by LC-MS. A total of 294 proteins were identified by LC-MS ( Figure 1B). Thirty-six of these proteins were trafficking-related proteins, including the well-known LDCV residents (Supplementary information, Table S1) syntaxin 1B, Rab3a, Rab3c, synaptotagmin 2 and vesicle-associated membrane protein 1 (VAMP1) [18][19][20][21]. Importantly, 8 GPCRs, 10 ion channels, 6 transporters and 70 signaling molecules were detected in the LDCVenriched fractions (Supplementary information, Table S1).…”
Section: Analysis Of the Protein Composition Of Ldcvsmentioning
confidence: 99%